Security Risks and Feature Limitations Impact on Productivity in Unauthorized Windows Usage - Rahmadani, Annisa (Universitas Tarumanagara, 2024)
Human connectivity. One dominant operating system is Windows. This research aims to investigate the security risks and usage of unofficial software, particularly in the context of Windows, the most widely used operating system in the world. Based on this background, the author conducted research using interview, survey, and literature review methods. Interviews with computer experts were conducted to understand the security issues and limitations of using unofficial Windows. It was found that unofficial Windows usage can result in security limitations, system disruptions, and limited functionality. Furthermore, the literature review revealed various security vulnerabilities in unofficial Windows and their impacts on users and organizations. Recommended solutions include switching to official Windows or Linux distributions, while increasing public awareness of the risks of using pirated software. Surveys were conducted to understand users' perceptions and experiences with unofficial Windows. The majority of respondents admitted to being uncertain about the security of the unofficial Windows operating system they used and experienced system disruptions or functional issues. Reasons for using unofficial Windows include a lack of understanding of the differences between official and unofficial versions, as well as their availability and lower cost. Thus, this research concludes that education on the risks of using pirated software is crucial to raising public awareness and promoting the use of safe and legal solutions ABSTRAK Dalam era digital yang semakin maju, perangkat lunak menjadi kunci bagi produktivitas, kreativitas, dan konektivitas manusia. Salah satu sistem operasi yang dominan adalah Windows, Penelitian ini bertujuan untuk menyelidiki risiko keamanan dan penggunaan perangkat lunak tidak resmi, khususnya dalam konteks Windows, yang merupakan sistem operasi yang paling banyak digunakan di dunia. Berdasarkan latar belakang tersebut, penulis menjalankan penelitian dengan metode wawancara, survei, dan studi pustaka. Wawancara dilakukan dengan ahli komputer untuk memahami masalah keamanan dan batasan penggunaan Windows tidak resmi. Ditemukan bahwa penggunaan Windows tidak resmi dapat mengakibatkan keterbatasan keamanan, gangguan sistem, dan fungsionalitas yang terbatas. Selanjutnya, studi pustaka mengungkapkan berbagai kerentanan keamanan dalam Windows tidak resmi serta dampaknya terhadap pengguna dan organisasi. Solusi yang disarankan adalah beralih ke Windows resmi atau distribusi Linux, dengan meningkatkan kesadaran masyarakat tentang risiko penggunaan perangkat lunak bajakan. Survei dilakukan untuk memahami persepsi dan pengalaman pengguna terhadap Windows tidak resmi. Mayoritas responden mengaku tidak yakin dengan keamanan sistem operasi Windows tidak resmi yang mereka gunakan dan mengalami gangguan sistem atau masalah fungsionalitas. Alasan penggunaan Windows tidak resmi antara lain kurangnya pemahaman tentang perbedaan versi resmi dan tidak resmi serta ketersediaan dan harga yang lebih murah. Dengan demikian, penelitian ini menyimpulkan bahwa edukasi tentang risiko penggunaan perangkat lunak bajakan penting untuk meningkatkan kesadaran masyarakat dan mendorong penggunaan solusi yang aman dan legal.